Homosexuality in the Pontifical Biblical Commission Document "What Is Man"? - Healy, Mary (The Biblical Annals, 2022)
Considerable public attention has been given to the treatment of homosexuality in the recent document of the Pontifical Biblical Commission, What Is Man? A Journey through Biblical Anthropology. Some reports have claimed that the document represents a shift in Catholic teaching toward the acceptance of homosexual acts. This article assesses that claim by carefully examining the relevant sections of the document in the perspective of its wider reflections on biblical anthropology and on the biblical vision of the institution of marriage. While the document situates the biblical texts concerning homosexuality within their literary and cultural contexts and emphasises the pastoral sensitivity with which this topic must be approached, it does not promote a revision or reversal of the Church’s teaching on sexual morality.